Combination of Searches for Invisible Higgs Boson Decays with the ATLAS Experiment - Aaboud, M; Aad, G; Abbott, B; Abbott, D C; Abdinov, O; Abed Abud, A; Abhayasinghe, D K; Abidi, S H; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; et al. (Physical review letters, 2019)
Dark matter particles, if sufficiently light, may be produced in decays of the Higgs boson. This Letter presents a statistical combination of searches for H→invisible decays where H is produced according to the standard model via vector boson fusion, Z(ℓℓ)H, and W/Z(had)H, all performed with the ATLAS detector using 36.1 fb^{-1} of pp collisions at a center-of-mass energy of sqrt[s]=13 TeV at the LHC. In combination with the results at sqrt[s]=7 and 8 TeV, an exclusion limit on the H→invisible branching ratio of 0.26(0.17_{-0.05}^{+0.07}) at 95% confidence level is observed (expected).